External Effects of Renewable Energy Projects: Life Cycle Analysis-based Approach - Salnikova, Anastasia; Chepurko, Yuri; Starkova, Nadezhda; HoÃ ng, Hiá»ƒn Nguyá»…n (International Journal of Energy Economics and Policy, 2019)
Nowadays planning and developing of innovative renewable energy projects across the globe imply calculation and consideration of negative environmental effects not only at the stage of utilization but also at the stage of manufacturing and disposal. Thus, the modern practice of environmental management on a regional level requires the more widespread introduction of life cycle analysis. The aim of the present paper is to develop an environmental effects evaluation methodology based on ecological impact categories through all the stages of lifecycle of renewable energy technologies. We used DEA-based calculation of the efficiency score for each renewable energy technology. EcoInvent database which rests on CML 2001 methodology has been chosen as a source of eco-indicators. We suppose, the efficiency ratio will remain unchanged, when transferring estimates of the life cycle of renewable energy facilities to another territory. This allows us to use data obtained in other regions of the world, to extrapolate comparative assessments and make the choice of the most environmentally preferable technology. The input-oriented DEA modelling has demonstrated geothermal and biogas technologies are the most preferable from an environmental point of view with the highest possible score. The least effective technologies are both modifications of PV with the minimum efficiency score. The results of the presented work might be useful for decision- and policymakers for a more consistent planning and energy strategy deployment. Keywords: renewable projects, external effects, LCA analysis, ecological impact JEL Classifications: O33, Q42, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.7959